Oral presentation anxiety in the English for academic writing classroom: a thematic analysis - Kartar Singh, Kulwant Kaur; Santakh Singh, Baljit Kaur (Pusat Pengajian Citra Universiti, UKM, 2024)
Most undergraduates are expected to go through oral presentations and public speaking at their universities. Oral presentations are conducted as a method of assessment in most university courses which emphasise students’ performance. Based on previous research, there is a significant number of students who struggle during oral presentations. Hence, this qualitative study aimed to identify the causes of speaking anxiety among undergraduates at the International Islamic University Malaysia (IIUM) and to explore strategies to mitigate this issue. Five students who enrolled in the English for Academic Writing (EAW) course at IIUM's Gombak Campus were selected for this study. A qualitative research method was employed, which included face-to-face interviews and thematic analysis was used to gather data and identify recurring themes. Through these interviews, the study highlighted specific fears that students relate to oral presentations and strategies to minimise their anxieties. The findings paved the way to reduce negative effects on students’ higher education experiences. This study is significant as the issue of public speaking fear among students needs to be addressed, and students need adequate support to overcome these challenges. The insights derived from this study provided valuable guidance for alleviating speaking anxiety, ultimately improving students’ academic and professional communication skills to meet the demands of their universities and future careers.